Large scale in vivo micro-RNA loss of function screen identified miR-29a, miR-100 and miR-155 as modulators of radioresistance and tumor-stroma communication - Golestaneh, Azadeh Fahim; Lecker, Laura S. M.; Nowrouzi, Ali; Schwager, Christian; Meister, Sarah; Weichert, Wilko; Debus, Jürgen; Abdollahi, Amir (International journal of cancer, 2019)
Micro RNAs (miR) are master regulators of cellular transcriptome. We aimed to investigate the role of miR regulation on tumor radiosensitivity and development of local tumor recurrence by a novel large-scale in vivo loss of function screen. For stable miR silencing, human A431 tumor cells were transduced with lentiviral constructs against 170 validated human miR (miRzip library). Fractionated radiotherapy (5x6Gy) was applied to A431 miRzip library growing s.c. in NCr nude mice. Enrichment of miRZip and miR expression was assessed using multiplexed qRT-PCR. The modulatory effect of miR on tumor and tumor microenvironment response to ionizing radiation was further evaluated by clonogenic survival, apoptosis (Caspase 3/7), DNA double-strand breaks (DSB, nuclear γH2AX foci), tumor microvessel density (MVD), transcriptome and protein analysis. Fractionated irradiation of the A431 miRzip library led to regression of tumors. However, after a latency period, tumors ultimately progressed and formed local recurrences indicating the survival of a subpopulation of miRzip expressing tumor clones. Among the selected miR for subsequent validation studies, loss of miR-29a, miR-100 and miR-155 was found to enhance clonogenic survival, reduce apoptosis and residual γH2AX foci of irradiated tumor cells. Moreover, knockdown of miR increased tumor angiogenesis correlating with elevated VEGF and TGFα expression levels. This phenomenon was most evident after tumor irradiation in vivo suggesting a critical role for tumor-stroma communication in development of the radioresistant phenotype. Engineering radioresistant tumors in vivo by modulating miR expression may lead to identification of critical targets for conquering local therapy failure.
Gesehen am 25.07.2019
Online 26 Nov 2018